Perception, Dreams, Films: Iconicity and Indexicality in Peirce's Theory of Perception - Dymek, Anne (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2013)
Chronologically speaking, Charles S. Peirce (1839-1914) could have mentioned the technique of film in the context of his phenomenological, or as he called them, phaneroscopic theories. But when he compared the human percepts to “moving pictures accompanied by sounds and feelings” in 1905 (MS 939 : 24), Peirce did not speak of the cinema. However, his investigations in the fields of cognition and phenomenology show relevant intersections with major concepts and problems of filmic perception theory. The present article aspires to investigate Peircian philosophy and film theory through some of their common concepts. The question will be raised as to whether the filmic viewing situation can be understood as a genuine perceptual situation in the Peircian sense. In a first step, I will give an analysis of Peirce’s theory of perception. In contrast to the majority of interpretations of the latter, which emphasize its iconic character, I shall argue for a perceptual process where iconicity is not the starting point but rather the outcome of it. This will imply an analysis of the roles of iconicity and indexicality in perception and of their relation to cinema’s “impression of reality”. Despite the phenomenological realism of cinematic images, the nature of what the viewer actually perceives is not as obvious as one might be tempted to think. Finally, an interpretation of filmic images as “diagrams of perception” will open up to some pedagogical dimensions of film viewing.